(3YeOI GdWGdH aj fSH Bd CHj WGdHs - (3GdOGhOqj GdWGdHoqi GdMSfj, CHh GdYHGS, GHf YfHI, LeGd GdOjf, CMeO Hf Ydj Hf MSjf, J (B828 (3g`s ((3YHGS Hf Ydj Hf MSjf GdMdj GdYPGQjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEf Yde GdfSH Yde YXje GdebOGQ SGWY GdCfhGQ CTGQ GdcJGH GdEdgj Edjg abGd (B{ (3hLYdfGce TYhHG hbHGFd dJYGQahG (B} (3Edi Jageg hMK GdfHj GdCej Ydjg abGd (B" (3JYdehG CfSGHce dJUdhG CYeGQce (B"..s
(3BNQgG (B:s
... (3hGdMLI GdTQja GdYeQj TjN hGdOg CHh GdZfGFe hgh CHh Ydj YeQ Hf Ydj Hf GdMSjf Hf YHO Gddg GdePchQ hgh GdeYQha HGdehVM GdfSGHg hefge GdMSjf Hf eMeO GdUhaj (B...(3Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3hQO GSe GdcJGH aj eYLe GdeDdajf HGSe (B( (3YOI GdWGdH (B)s
(3JHUQI GdeDda (B:s
(3aj cTa GdXfhf(B: (3dLeGd GdOjf(B: (3CMeO, GdeYQha(B: (3HGHf YbHI(B. ( (3HGdbGa GdeKfGI GdahbjI (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\177s
Keywords: (3GdJGQjNs